Perception of High Alcohol Use of Peers Is Associated With High Personal Alcohol Use in First-Year University Students in Three Central and Eastern European Countries. (28th July 2016) - Helmer, Stefanie M.; Sebena, Rene; McAlaney, John; Petkeviciene, Janina; Salonna, Ferdinand; Lukács, Andrea; Mikolajczyk, Rafael T.
ABSTRACT: Objectives : The objectives of this study were to assess discrepancies between estimated peer and personal drinking behavior and to determine associations between perceptions of peer and personal drinking behavior among university students from Hungary (HU), Lithuania (LT), and the Slovak Republic (SK). Methods : 2, 554 freshman university students completed an online questionnaire on the frequency of their personal alcohol use, the number of heavy drinking occasions and on their perception concerning the corresponding drinking behavior of a typical student. Associations between perceived peer and personal use were analyzed by means of logistic regression, adjusting for sex. Results : The majority of students across all countries thought their peers drink more frequently and are more often involved in heavy drinking occasions than themselves. Students who perceived the frequency of peer alcohol use to be higher were more likely to drink alcohol twice a week or more often (SR: OR = 3.81, 95% CI = 2.51–5.79; LT: OR = 3.16, 95% CI = 2.11–4.75; HU: OR = 2.10, 95% CI = 1.53–2.87) compared with students who drink alcohol monthly or less. Those who perceived the number of peer heavy drinking occasions as high were more likely to report heavy drinking weekly or more often (SR: OR = 3.16, 95% CI = 1.92–5.20; LT:OR = 3.56, 95% CI = 2.14–5.94; HU:OR = 1.41, 95% CI = 0.79–2.51) compared with students who report heavy drinking less than monthly. Conclusions/Importance : University students perceived peer alcohol use to be higher than their personal use. Given the association between perceptions and personal alcohol use, future research should investigate if targeting perceptions in the surveyed countries may have an impact on alcohol use.